Analisis Strategi Traditional Travel Agency Di Tengah Persaingan Online Travel Agency (Studi Kasus: Airlangga Travel) - Almira, Winona; Alodia, Wiguna Alodia (Jurnal Manajemen, 2019)
The travel industry in Indonesia is still very attractive, especially when considering the large population of Indonesia and the growing value trend of the travel market. However, the development of information technology and the internet has had an impact on the proliferation of Online Travel Agencies (OTA), resulting in high levels of competition in the travel industry. Traditional travel companies must continue to innovate to maintain their presence in the competition. This research was conducted to analyze the competitive conditions of the travel industry in Indonesia, a case study at Airlangga Travel company. The research method uses Porter and SWOT analysis. The results of the study are recommendations for differentiation strategies for Airlangga Travel in order to survive in the intense competition of the travel business